Penerapan Yuridis Hak Cuti Bagi Pekerja dalam Pasca Berlakunya Undang-Undang Cipta Kerja Nomor 11 Tahun 2020 (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The Job Creation Law Number 11 of 2020 brings significant changes to various aspects of employment, including workers' leave rights. This article aims to analyze the juridical application of leave rights after the enactment of the law, focusing on the changes that have occurred and their impact on the relationship between workers and employers. While leave rights such as annual leave, maternity leave, and sick leave are still recognized, detailed arrangements regarding the implementation of leave are left to implementing regulations or work agreements. This flexibility provides employers with advantages in workforce management, but raises concerns about potential reductions in workers' rights. The article concludes that these changes must be responded to with fair and transparent policies to maintain a balance between employers' interests and workers' welfare. The research in this paper uses a descriptive analytical research method. This method describes data from various sources, including statutory regulations, journals, and other sources from the internet concerning events that occurred in society.